Sport, eksport og selvstændighedskamp - Mortensen, Rune Ryelund (Forum for Idræt, 2007)
Artiklen beskriver hvordan den uofficielle landskamp i 2001 mellem Tibet og Grønland, af landene blev brugt som redskab i forfølgelsen af politiske interesser. Rune Ryelund Mortensen: Sport, export and national identity This article examines the debate and diplomatic activity surrounding the soccer match between Greenland and Tibet on June 30th 2001. The article tells the story of how the involved persons and organisations tried to promote their positions through use of the media, economical, and political pressure. The article investigates the roles of the Greenland Home Rule, Government and Office of Foreign Affairs, the Ministry of Foreign Affairs in Denmark, The Chinese Embassy in Copenhagen, the Greenlandic Sea Fishery and Export Association, Royal Greenland, Greenlandic Sporting Association and Tibetan National Football Association in the debate and diplomatic activity prior to the match. The focus is on the combination of sports and politics, and the use of sport to pursue political, nationalistic and cultural goals. The article is based on the media coverage, personal interviews and documents from the above mentioned organisations.